The influence of motivation and habit on acceptance of elementary school students using Google Classroom - Zulherman Zulherman; Putri Alya Diana; Ikbar Salsabila; Elsa Ananda Putri; Hanifah May Wisuda Ashari; Mardhiyah Widya Ningsih (International Journal of Evaluation and Research in Education (IJERE), 2023)
This study aimed to prove the factors that influence elementary school students’ interest in using the Google Classroom platform. This study also used a technology acceptance model (TAM) theory approach by adding external variables, namely motivation and habit, to the study. The survey method was conducted to collect data from 209 elementary school students. We analyzed the data using the structural equation modeling (SEM) PLS 3.0 application. The study’s results showed that one hypothesis was rejected: Motivation had no significant effect on perceived usefulness. In contrast, the other seven hypotheses had a significant positive effect. Research suggested that the habit factor fits the theoretical approach of the TAM model.